First International Congress of Systematic and Evolutionary Biology - James L. Reveal (Hello World!, 1971)
The Society of Systematic Zoology and the International Association for Plant Taxonomy have joined forces to develop this first opportunity for botanical/zoological interaction at the international level. The University of Colorado (Boulder, Colorado) has extended a gracious invitation to meet on that campus